Liability For Processing Personal Data At Private Universities Related to Personal Data Protection Based On Indonesian Law - Joddy Mulyasetya Putra; Gunardi Lie (LPPM Universitas Ekasakti Padang, 2023)
Technological advances are like two sides of a coin that have several conditions that are not only beneficial but need to be aware of the dangers, one of which is data leakage. Data leakage does not always occur intentionally, it can occur due to the negligence of a software itself due to the weakness of its device security system. Personal data is crucial in this era of digitalization, which all of them need, including in educational institutions such as private universities. Foundations and Private Universities have a legal relationship as stipulated in the Foundation Law adjusted to the agreement made by both. Foundations and Private Universities have their respective portions in terms of their duties, functions, authorities, and responsibilities including in the management of personal data if there is a data leak who is the data controller and data processor. The type of research used is doctrinal law through the search for library materials and secondary data consisting of primary documents, secondary legal documents and non-legal documents. The research conducted will later examine the relevant legislation that regulates associated with the legal issues raised whether appropriate or not in its implementation. The results showed that based on the legal relationship, the Foundation as a controller of personal data and the Cooperative as a personal data processor. Both have their respective portions of responsibility and if there is a data leak, the responsibility is borne by the foundation stakeholder as the controller of personal data and the corporation as the beneficiary.